An opportunity to commercialize the religious spiritual tourism industry and its capabilities in Algeria - Zidelkhir, Miloud; Kadri, Med Tahar (Dirassat Journal Economic Issue, 2013)
The spiritual tourism is an opportunity and a motor of investment in the tourism, when the Algerian economy seeks to benefit it. And it may be the optimal model between any alternates aim to liberate the economy for oneness of the oil and petroleum industry as a since resource. In this article, we may be describing the different change in the local and the international environment and the vanishing of the petroleum. After, we can present the tourism sector, than is a perfect solution to this problem. We indicate the particularity case of the spiritual tourism and his capacity. In the ending, we may concluded that is necessary for our Algeria to deployed a lot in the marketing activities in the spiritual tourism.